Measurements of ambient ozone using indigo blue-coated filters - Felix, E. P.; de Souza, KAD; Dias, C. M.; Cardoso, Arnaldo Alves [UNESP] (Aoac International, 2006)
Ozone monitoring techniques utilize expensive instruments that are often large and heavy. These instruments are not easy to handle in the field, and their size also limits some sampling schemes, principally for indoor ozone determination. We have developed a lightweight, inexpensive, and sensitive method that offers flexibility to undertake measurements of ambient ozone in many environments, both indoor and outdoor. The method is based on the reaction of ozone with indigo blue dye. The indigo molecule contains 1 carbon double bond (C = C) that reacts with ozone and results in nearly colorless reaction products. During sample collection, 2 cellulose filters coated with 40 mu L of 1.0 x 10(-3) M indigo blue were used. The determinations were done spectrophotometrically at 250 and 600 nm. The analytical parameters studied were sampling time and flow rate. Analytical curves were constructed with concentrations ranging from 37 to 123 parts per billion by volume (ppbv) of standard ozone, at 0.4 L/min and 15 min sampling time. The detection limits achieved were 6 and 9 ppbv, respectively, at 250 and 600 nm. Considering interferences, measurements made at 250 nm gave more reliable and specific values for ozone.